2020
DOI: 10.1007/s10555-020-09844-3
|View full text |Cite
|
Sign up to set email alerts
|

What recent primary studies tell us about ovarian teratomas in children: a scoping review

Abstract: Our knowledge of ovarian teratomas in children is still far from complete, and much remains to be discovered. Here, we conduct a scoping review of the primary research related to ovarian teratomas in pediatric age. To our knowledge, there is no published synthesis of the literature surrounding ovarian teratomas in children using scoping review methodology. We identified 24 studies from 11 countries; 18 studies were retrospective, 3 were prospective, and 3 were experimental. There were 6 studies concerning matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…As the EFS curve did not show any plateau, it suggests the need for prolonged surveillance after surgery 18,28 . Despite the lack of guidelines regarding the FU after OMT resection in children, and considering the median time to a second event of 30.5 months, we suggest a pelvic and abdominal US exam every 6 months during the 5 years following initial surgery.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…As the EFS curve did not show any plateau, it suggests the need for prolonged surveillance after surgery 18,28 . Despite the lack of guidelines regarding the FU after OMT resection in children, and considering the median time to a second event of 30.5 months, we suggest a pelvic and abdominal US exam every 6 months during the 5 years following initial surgery.…”
Section: Discussionmentioning
confidence: 83%
“…Information on the management of second events and long‐term morbidity was also retrieved through the reports of the postoperative consultations where abdominal ultrasound (US) was carried out. In the absence of consensus in the literature, the schedule of this follow‐up (FU) program differed from one center to another 17–19 …”
Section: Methodsmentioning
confidence: 99%
“…As the EFS curve did not show any plateau, it suggests the need for prolonged surveillance after surgery (18). Considering the median time to a second event of 30.5 months and the slow growth rate of this benign tumor, we propose a pelvic and abdominal US exam every 6 months during the five years following initial surgery.…”
Section: Discussionmentioning
confidence: 96%
“…Information on the management of second events and long-term morbidity was also retrieved through the reports of the postoperative consultations where abdominal ultrasound was carried out. In the absence of consensus in the literature (17)(18)(19), the schedule of this follow-up (FU) program differed from one center to another.…”
Section: Populationmentioning
confidence: 99%
“…The role of oophoropexy in treating ovarian torsion is still not clear (2, 9, 11). evidence based medicine for pediatric ovarian teratomas (6). The other systematic review reported by Renaud et al also has revealed lack of prospective and randomized trials (1).…”
Section: Discussionmentioning
confidence: 99%